Return on investment of the diabetes foot care clinical pathway implementation in Alberta, Canada. (July 2020) - Thanh, Nguyen X.; Dmytruk, Kathy; O'Connell, Petra; Rogers, Edwin; Fillier, Denise; MacRae, Jennifer M.; Thomas, Chandra; Rennie, Chantal; Eitzenberger, Christiane; Newman, Chryslyn; Match, Brian; Thompson, Charlotte; et al.
Abstract: Aims: Based on best practices, the diabetes foot care clinical pathway (DFCCP) has been developed and implemented in several clinics in Alberta, Canada. We performed a return on investment (ROI) analysis of this implementation. Methods: We used a cohort design comparing both cost and return (in terms of reduced health services utilization, HSU) between diabetes patients who were exposed and who were unexposed, to the intervention. We used a difference-in-difference approach and a propensity-score-matching technique to minimize biases due to differences in demographic and clinical characteristics between two cohorts. We used a 1-year time-horizon and converted all costs/savings to 2019 Canadian dollars (1 CA = 0.75 US). Results: The intervention helped avoid 3500 in costs of HSU per patient-year. Subtracting the intervention cost of 500, the net benefit of intervention was 3000 (ranged 2400–3700) per patient-year. The ROI ratio was estimated at 7.4 (ranged 6.1 to 8.8) meaning that every invested 1 returned 7.4 (ranged 6.1–8.8) for the health system. The probability of intervention being cost-saving ranged from 99.5–100%. Conclusions: The implementation of DFCCP in Alberta is cost-saving. A continuation of the pathway implementation at studied clinics and a spread to other clinics are recommended.